FRAMEWORK FOR SUSTAINABLE CONSTRUCTION WASTE MANAGEMENT PRACTICE AT SITE - YA'COB, ASYRAN SYAFIQ (2016)
The construction industry has been contributing significantly to the development of a country through its function in constructing buildings and other facilities. The industry, however, becomes one of the sources that pollute the environment by illegal dumping, open burning and etc. This issue points the need for better construction waste management as a whole. Therefore, this research aims to facilitate the construction stakeholders to improve current Construction Waste Management at site. In order to achieve the research aim, three objectives have been set which are firstly to investigate and assess the current sustainable practice CWM at construction sites in Malaysia, secondly to investigate factors that influence the effectiveness of SCWM at these sites and propose the action plan to ensure SCWM can be implemented effectively at site and the third objective is to propose a framework for Sustainable Construction Waste Management Practice at site.